Miscellaneous nomenclatural notes on Andean Chrysochlamys (Clusiaceae: Clusieae) - Caro-Sánchez, Angy V.; Marinho, Lucas C.; Idárraga-Piedrahíta, Alvaro; Alzate-Guarín, Fernando (Phytotaxa, 2024)
Chrysochlamys (Clusiaceae) is a strictly Neotropical genus that comprises between 35 and 55 species. The taxonomy of the genus is poorly-known in South American region, especially in Andean countries. During the taxonomic revision of Chrysochlamys and related genera in Colombia we observed two mainly gaps: the unclear nomenclatural history of Andean Chrysochlamys and the necessity of lectotypification of some species published by Pax, Poeppig, Planchon and Triana. To solve both issues, we provide a Chrysochlamys nomenclatural history summary and reduce nomenclatural ambiguities on a few Andean flora. For this, we carried out an exhaustive analysis of Chrysochlamys and related genera type collections and protologues. We propose a new combination, Chrysochlamys microcarpa comb. nov., originally published in Tovomita, designated six lectotypes, propose a numbering for three Triana’s type collections, and discuss a case of inadvertent lectotypification. This paper provides relevant information about problematic or understudied Chrysochlamys species, which will be useful for subsequent taxonomic studies.